Sensorized pacifier to evaluate non-nutritive sucking in newborns. Issue 4 (April 2016) - Grassi, Angela; Cecchi, Francesca; Sgherri, Giada; Guzzetta, Andrea; Gagliardi, Luigi; Laschi, Cecilia
Highlights: We developed a device for an objective measurement of non-nutritive sucking (NNS). The device is able to distinguish the NNS phases: suction and expression. Experimental tests confirmed the device as an adequate tool for measuring NNS patterns. The NNS rhythmicity was quantified with the extracted parameters. Abstract: We developed a device for an objective measurement of non-nutritive sucking (NNS). NNS is newborns' spontaneous action that is a predictor of their neural system development and can be adopted as an intervention to train oral feeding skills in preterms. Two miniaturized digital pressure sensors were embedded into a commercial pacifier and the two signals were simultaneously acquired using the Inter-Integrated circuit (I²C) interface. This solution traced a complete pressures profile of the sucking pattern in order to better understand the functional aspects of the two NNS phases, the suction and the expression. Experimental tests with nine newborns confirmed that the sensorized pacifier is an adequate tool for measuring NNS burst-pause patterns. The identified parameters related to the suction/expression rhythmicity could be used as indicators of the NNS ability. This device might be used both for exploring the possible diagnostic data contained in NNS pattern and for monitoring the sucking skills of premature infants.